EFFECT OF STUB ON THE PERFORMANCE OF 3-DB BRANCH LINE COUPLER FOR LOW-COST VECTOR NETWORK ANALYZER APPLICATION - ARLIZ, ABDUL SAMAT (Universiti Malaysia Sarawak (UNIMAS), 2019)
High Frequency (HF) technology is very important and common. With the highspeed telecommunications and wireless technology that is rapidly increasing, it is very important for electrical and electronics engineers to understand the basic Radio Frequency (RF) applications and then apply the knowledge in designing advanced RF applications in future. To assist the engineers and designers in achieving this goal, High Frequency Test Instrument is very important. One of the most useful test equipment for RF designers is Vector Network Analyzer. Unfortunately, the price of single VNA is very expensive and cost hundred thousand of Ringgit Malaysia. Thus, low cost VNA can be developed to reduce the cost needed to test the instruments in microwave. One of the way to develop low cost VNA is by producing microstrip design for the components inside the VNA especially the coupler. By integrating all of the components to build up the VNA into microstrip design, the cost of the VNA can be reduced effectively. Branch line coupler is commonly used due to its simplicity. Reducing the size of the coupler can provide cheaper fabrication and more space can be utilized for performance improvement.However, the great drawbacks of microstrip coupler is its narrow bandwidth which makes it unable to cater the high frequency of the VNA. Thus, to overcome the narrow bandwidth, stub will be implemented into the 3-dB microstrip branch line coupler design to improve the bandwidth performance. Few analysis of stub implementations have been done in this research project in order to investigate the effect of the different stubs’ designs towards the bandwidth improvement of the microstrip coupler. Based on the analysis, by implementing two stubs with width and length of 1 mm, positioned at location 0, which is at the centre of the microstrip coupler, shows best result with return loss of -57.98 dB and bandwidth has been improved from 1.09 GH z to 1.39 GHz compare to the conventional branch line coupler which is improved by 30.36%.